Promosi Melalui Video Iklan Berbasis Aplikasi Sony Vegas Pro 13 untuk Menarik Minat Beli di Kedai Kopi Kembang Malang - Fandy Achmad Maulana Roisdiansyah; Ahmad Fauzi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This research was an action research or a research using action research method. Data of the research was collected through observations, interview, questionnaire and documentation. The selected units of analysis were 1 business owner, 2 marketing experts, 2 computer experts and 30 consumers. EPIC Model was used as a calculation tool for design effectiveness and buying interest in this research. The results of the research showed that the video advertising that has been made was included in the very effective category. That was proved from the results of the EPIC rate calculation for the effectiveness of the video advertising design that has been made was 4,7 and the value of buying interest from the video advertising that has been made was 4,43. From that results of the research, it can be concluded that the video advertising is effective as a promotional media and able to attract consumer’s buying interest. For Kedai Kopi Kembang Malang, it is recommended to make more video contents regularly so consumers will be more interested and add other social media as promotional media such as TikTok and the others.